OWNERSHIP TYPE AND COMPANY PERFORMANCE: EMPIRICAL STUDIES IN THE INDONESIAN STOCK EXCHANGE - Soejono, Fransiska (Journal of Indonesian Economy and Business, 2010)
This study is aimed to test the difference in performance among companies withÂ various types of ownership (foreign, state, and private) on a sample of 206 companieslisted in ISE (Indonesian Stock Exchange) between 1999-2006 resulting in 795 company yearÂ observations. The ANCOVA model and multiple comparison methods are used to testÂ the hypothesis that private-owned companies have better performance than state-ownedÂ enterprises and foreign-owned companies have better performance than private-ownedÂ companies. Contrary with the hypothesis, the result shows that state-owned enterprisesÂ have better performance than private-owned companies. The possible explanation for thisÂ is because state-owned enterprises have more experience than private-owned companiesÂ (based on LogAge). State-owned firms may get some special facilities (including theÂ easiness to get debt funding) from government. The result also shows that foreign-ownedÂ companies have better performance than private-owned companies which support theÂ hypothesis. Foreign-owned companies have more experience in managing enterprises thanÂ private-owned companies. Furthermore, foreign-owned companies in some industries tendÂ to be more active in doing investment than private-owned companies. There are someÂ implications of these results. First, different ownership type gives different effect to thecompanyâs performance. Second, government can consider foreign ownership in itsÂ privatization policy.Keywords: Ownership type, Performance, Experience, Investment.